APLIKASI PENCARIAN LOKASI DAN INFORMASI TAMAN PENDIDIKAN AL-QUR’AN KOTA KUPANG BERBASIS ANDROID - Hariyanto, Rudi; Malahina, Edwin A. U.; Sumarlin, Sumarlin (STIKOM Uyelindo Kupang, 2020)
Kupang city is one of the cities in Indonesia that has a high level of religious tolerance, this is supported by the Peace Gong archipelago, but this is inversely proportional to religious education in the city of Kupang, especially the Islamic religious education because of lack of religious instruction in formal education institutions . The Qur'an Educational Park is an institution that plays an important role in providing religious education, the procedure of reading and understanding al-quran. But the lack of community knowledge about the location of the Quranic Education Park has left the public confused to find and choose the right religious education institutions to give their children education about religion. For that, there need to be built an application that can display the location and information about the Qur'an Educational Park located in the city of Kupang. With Android-based development, it will simplify the community because Android smartphone users are quite a lot and ensure the accuracy of user location data. In addition to showing the location, the application will also provide information about the Qur'an Educational Park in Kupang City that has been marked on google maps.